The study of the acceptance toward Mandarin language course among student / Wilson Johnny Jaen and Yusuf Mohd Nassir - Johnny Jaen, Wilson; Mohd Nassir, Yusuf (2009)
This study was done to observe and analyze the degree of acceptance toward mandarin language course among degree level students in UiTM Samarahan campus. Generally the mandarin language course in UiTM was offered as elective course to those who are in bachelor programme. The mandarin language course was divided into 3 different levels of stages as students must past the first level in order to proceed to another level of the mandarin language course. These aspects show that how far the students’ acceptance toward the language as it may be difficult to certain students. The objectives of this study includes to measure the degree of acceptance among the students towards the Mandarin language course, to identify the factors that leads to the students preferences towards the mandarin language course and to suggest way on how to improve the students understanding on mandarin language course.